Finance and Sustainability Proceedings from the Finance and Sustainability Conference, Wroclaw 2017 - Bem, Agnieszka; Daszyńska-Żygadło, Karolina; Hajdíková, Taťána; Juhász, Péter (Springer Proceedings in Business and Economics, 2018)
XI, 284 p. 29 illus., 6 illus. in color.